Citizen participation in popular festivals in Colombian Caribbean region: A Quantitative Analysis of Carnival of Barranquilla and Independence Feasts of Cartagena (2022)
The research analyzes the citizen participation in cultural activities, in particular, in the most popular celebrations in the Colombian Caribbean region, the Carnival of Barranquilla Carnival and the Independence Feasts of Cartagena, whose historical links and evolution have been decisive in the construction of the regional festive memory. The approach and method of Cultural Economics are used to identify and compare the factors associated with local participation during the last decade, and Como Vamos programs’ surveys are used to empirically evaluate the role of a set of traditional variables and the local context in the decision to participate in these festivals. The results suggest wide gaps between and within cities, which are explained by variables such as cultural capital, gender and leisure time, and others considered as structural, such as socioeconomic status, poverty and place of residence. Inequities are substantially greater in Cartagena, where it is necessary to expand access to the most lagging population. The article offers a new standpoint on the nature of regional feast and festivals and inputs for designing cultural policies to greater social appropriation of the regional intangible heritage. © 2022 Universidad del Norte. All rights reserved.